2021
DOI: 10.1016/j.jbc.2021.100286
|View full text |Cite
|
Sign up to set email alerts
|

Pantoea stewartii WceF is a glycan biofilm-modifying enzyme with a bacteriophage tailspike-like fold

Abstract: Pathogenic microorganisms often reside in glycan-based biofilms. Concentration and chain length distribution of these mostly anionic exopolysaccharides (EPS) determine the overall biophysical properties of a biofilm and result in a highly viscous environment. Bacterial communities regulate this biofilm state via intracellular small-molecule signaling to initiate EPS synthesis. Reorganization or degradation of this glycan matrix, however, requires the action of extracellular glycosidases.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In previous studies, it was found that INA bacteria, Pantoea stewartii , is able to secrete WceF, an enzyme which is able to cleaves stewartan exopolysaccharide [ 49 ]. Other studies also found that aqueous extract of Enterobacter sp., inhibits Biofilm of staphylococcal [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was found that INA bacteria, Pantoea stewartii , is able to secrete WceF, an enzyme which is able to cleaves stewartan exopolysaccharide [ 49 ]. Other studies also found that aqueous extract of Enterobacter sp., inhibits Biofilm of staphylococcal [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to AlphaFold2, the 110 N-terminal residues of gp526 form a six-stranded beta sandwich preceded by an α-helix, i.e., a fold similar to that of the head domain D1 of CBA120 TSP1 (4oj6 [30]). The body of gp526 (residues 113-432) comprises two triangular domains (of which one, BD1, is similar to a Knob 2 domain of P. aeruginosa R1 pyocin fiber PALES_06171; 6cl5 [55]) and a large β-sandwich domain, which was a good match to that of a glycan biofilm-modifying enzyme WceF from Pantoea stewartii (6tgf [59]). Another β-sandwich domain is located at the gp526 C-terminus and, according to Dali, its structural homolog is also present in the TSP from Acinetobacter baumanii phage phiAB6 (5jse [60]).…”
Section: In Silico Analysis Of Rak2 Tfpsmentioning
confidence: 99%
“…While a CD search failed to identify any conserved domains that would imply EPS depolymerase activity for either of these three proteins, the top HHpred hit for each of the three of them was to a PDB structure (6TGF_E; probabilities ≥ 99.92, e-values ≤ 4.5 × 10 −24 ), representing a Pantoea stewartii WceF-a glycan biofilm-modifying enzyme with a bacteriophage tailspike-like parallel beta-helix fold. It was recently shown that WceF is a glycosidase active on stewartan, which acts as the main P. stewartii EPS biofilm component, and that WceF is very similar to bacteriophage tailspike proteins [51]. The same authors also noted that WceF homologs are also present in other plant pathogens of bacterial origin, but the functional role of these proteins is so far not fully understood [51].…”
Section: Pantoea Phage Nafs113mentioning
confidence: 99%
“…It was recently shown that WceF is a glycosidase active on stewartan, which acts as the main P. stewartii EPS biofilm component, and that WceF is very similar to bacteriophage tailspike proteins [51]. The same authors also noted that WceF homologs are also present in other plant pathogens of bacterial origin, but the functional role of these proteins is so far not fully understood [51]. Although ORFs encoding these products overlapped in the genome of Nafs113 by about 30 bp, they were in +1 and +3 reading frames, respectively.…”
Section: Pantoea Phage Nafs113mentioning
confidence: 99%